2023
DOI: 10.1186/s12905-023-02314-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between covid-pandemic anxiety and sleep disorder with menstrual disorders among female medical workers

Abstract: Background It has been more than 2 years since the 2019 novel coronavirus disease (COVID-19) pandemic destabilized the world, adversely affecting not only physical health, but also mental health. During this time, frontline medical workers were at a greater health risk, especially female medical workers. Changes or abnormalities in the menstrual cycle—an important indicator of women’s health—may jeopardize female reproductive functioning. Considering that emotional health and sleep status may b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…One more important point to keep in mind is the effect of the COVID-19 pandemic revealed that menstruation in female medical workers was more affected by COVID-19. This topic mandates regular exercise and good physical condition to act as protective factors, while anxiety and insomnia were risk factors for menstrual abnormalities [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…One more important point to keep in mind is the effect of the COVID-19 pandemic revealed that menstruation in female medical workers was more affected by COVID-19. This topic mandates regular exercise and good physical condition to act as protective factors, while anxiety and insomnia were risk factors for menstrual abnormalities [21][22][23].…”
Section: Discussionmentioning
confidence: 99%